Sulfur Deposition and Poisoning of La0.6Sr0.4Co0.2Fe0.8O3-[delta] Cathode Materials of Solid Oxide Fuel Cells - Wang, C.; Chen, Kongfa; Jiang, San Ping (The Electrochemical Society, Inc, 2014)
Sulfur in the air stream is one of the major contaminants affecting the performance stability of cathodes of solid oxide fuel cells (SOFCs) such as La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) perovskite. Here sulfur deposition and poisoning was investigated on LSCF bar samples in the presence of 20 ppm SO2 and temperature range of 400–900°C, using scanning electron microscopy, confocal laser Raman spectroscopy and electrical conductivity relaxation (ECR) methods. Sulfur (SO2) reacts with LSCF, primarily forming SrSO4 at high temperatures (i.e., ≥ 700°C) and SrS at low temperatures (i.e. <700°C). Surface segregated SrO plays an important role in the sulfur deposition. The most important observation of this study is that sulfur deposition shows a distinct volcano-type dependency on the heat-treatment temperature and is most pronounced at temperatures around 700°C, indicating that the reaction rate between the segregated SrO and SO2 is highest at ∼700°C. The ECR results indicate that the surface exchange coefficient of LSCF after the exposure to 20 ppm SO2 at 700, 800 and 900°C for 48 h is two orders of magnitude lower than that of the sample tested in the absence of SO2, indicating that sulfur poisoning deteriorates significantly the surface exchange and diffusion processes for the O2 reduction reaction on LSCF electrodes.